2020
DOI: 10.20944/preprints202012.0304.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryopreservation for Tree Species with Recalcitrant Seeds: the Avocado Case

Abstract: Recent developments in the cryopreservation space has increased the trend in germplasm collections established through cryopreserved in vitro material. Cryopreservation of recalcitrant seeds through embryos and embryonic axes, is not uncommon. Tropical and sub-tropical plants are not acclimated to the cold season, therefore have no in-built natural resilience to the cold. Also, larger seeds from trees, such as avocado (Persea americana Mill.), mango (Mangifera indica) and durian (Durio zibethinus L.) are sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
0
5
0
2
Order By: Relevance
“…The findings in the present study were similar to previously published results. In a study carried out by O'Brien et al (2020), it was reported that the survival rate in avocado increased in the media containing 100 and 250 mg L -1 AA. In the study conducted by Ahmad et al (2016), it was found that using AC, ASA and CA alone increased the survival rate in guava.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings in the present study were similar to previously published results. In a study carried out by O'Brien et al (2020), it was reported that the survival rate in avocado increased in the media containing 100 and 250 mg L -1 AA. In the study conducted by Ahmad et al (2016), it was found that using AC, ASA and CA alone increased the survival rate in guava.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study were similar to some previous researches. In these studies, it has been reported that the application of AC, ASA, CA together to avocado explants gave better results than the application alone in terms of browning intensity (Nel et al, 1983;Pliego-Alfaro and Murashige, 1987;O'Brien et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…armazenadas hidratadas e em câmara fria. Goldbach (1979) BARBEDO, 2014;DAVIES et al, 2018;STRECZYNSKI et al, 2019;BHARUTH & NAIDOO, 2020;O'BRIEN et al, 2020;BALLESTEROS et al, 2021).…”
Section: Sementes Recalcitrantes Versus Ortodoxas E Sua Conservaçãounclassified
“…O armazenamento de sementes geralmente oferece o mais seguro, eficiente e barato método de conservação, entretanto, para espécies que produzem sementes com alta recalcitrância o processo não é fácil e, muito menos simples (CORNIBEAU & CÔME, 1988). Razão pela qual houve, nas últimas décadas, forte incentivo à procura de métodos que ampliassem o período de armazenamento de tais sementes, e os menores avanços em técnicas de armazenamento, tão difíceis de se conseguir para essas espécies, foram e são de grande valia para os bancos de germoplasmas (BÖRNER & KHLESTKINA, 2019;BHARUTH & NAIDOO, 2020;O'BRIEN et al, 2020). Ainda assim, os resultados de muitas e aprofundadas pesquisas demonstram que, a única opção viável para a conservação a longo prazo de germoplasma de espécies produtoras de sementes recalcitrantes é a criopreservação (GONZALES-BENITO & PEREZ-RUIZ, 1992;HOR et al, 2005;WALTERS et al, 2013;PAMMENTER & BERJAK, 2014;DAVIES et al, 2018;STRECZYNSKI et al, 2019;BHARUTH & NAIDOO, 2020;O'BRIEN et al, 2020;BALLESTEROS et al, 2021).…”
Section: Introductionunclassified